Above-ground woody biomass distribution in Amazonian floodplain forests: Effects of hydroperiod and substrate properties - Assis, Rafael Leandro de; Wittmann, Florian Karl; Bredin, Yennie K.; Schöngart, Jochen; Quesada, Carlos Alberto Nobre; Piedade, Maria Teresa Fernandez; Haugaasen, Torbjørn (Forest Ecology and Management, 2019)
The importance of tropical forests in regulating global carbon stocks is well known. However, the role of abiotic variables related to climate conditions and edaphic parameters for patterns of above-ground woody biomass (AGWB) are still under debate. For Amazonian forests subjected to periodic floods, these patterns are even more uncertain. This study aimed to evaluate AGWB stocks in Amazonian floodplain forest, and investigate the importance of forest structure, hydroperiod and edaphic parameters for AGWB. Results are based on floristic inventories conducted in twelve hectares of forest distributed across four floodplains. All trees ≥10 cm DBH were tagged, identified, and had their DBH and height measured. Allometric equations were applied for calculating AGWB. Hydroperiod was estimated for each sample plot, and soil samples were collected and chemical and physical components analyzed. Hierarchical partitioning was applied to determine importance of forest structure variables for AGWB, and GLMMs to evaluate the individual role of several edaphic parameters and hydroperiod for AGWB stocks. AGWB estimates varied substantially both between and within sites, as did the proportional contribution of forest structure variables to AGWB. Fabaceae contributed most to AGWB overall, and hydroperiod was more important than soil fertility in explaining variation in AGWB values. Amongst the edaphic variables, Iron (Fe) was the component that influenced AGWB the most, followed by Aluminium (Al) and Phosphorus (P). Overall, our results indicate that, on the investigated Amazonian floodplains, AGWB is mainly driven by hydroperiod rather than edaphic properties. This occurs despite a constant input of nutrients caused by flooding events. In addition, this is the first study to suggest that P appears to be of some importance in Amazonian várzea and paleo-várzea floodplains, where soil fertility is generally higher than in non-flooded terra firme forests. © 2018 Elsevier B.V.
Keywords: Banks (bodies Of Water); Biomass; Chemical Analysis; Floods; Nutrients; Soils; Above-ground Woody Biomass; Flood-plains; Forest Structure; Hydroperiods; Soil Nutrients; Forestry; Aboveground Biomass; Allometry; Diameter; Flood; Floodplain Forest; Height; Hydroperiod; Legume; Soil Nutrient; Soil Property; Spatial Distribution; Stand Structure; Substrate; Tropical Forest; Woody Plant; Biomass; Chemical Analysis; Floods; Forestry; Forests; Nutrients; Soil; Variables; Amazonia; Fabaceae